Gastrointestinal involvement in Henoch Schonlein purpura : A Case Report - Che Mohamed, Siti Kamariah; Yunus, Rohaizan (Faculty of Medicine, International Islamic University Malaysia, 2009)
Henoch-Schonlein purpura or anaphylactoid purpura is a systemic vasculitis of unknown cause that affects small vessels and mainly involves the skin, joints, gastrointestinal tract and kidneys. Gastrointestinal involvement occurs in more than half of patients and is thought to be related to edema and intramural haemorrhage. Radiologically the gastrointestinal findings are mainly those of bowel ischemia with “thumbprinting” and bowel wall oedema. Although this disease is usually treated conservatively, aggressive intervention is occasionally performed because of acute abdominal symptoms due to complications, such as perforation, intussusception and obstruction. This report illustrates a case of Henoch-Schonlein purpura with acute abdominal symptoms due to intussusception.